MOTIVATION OF THE PUBLICATION ACTIVITY OF LECTURERS IN A MEDICAL UNIVERSITY - A.M.DUYSENOVA (Avicenna Tajik State Medical University, 2022)
Objective: To study and evaluate the impact and/or connection between the financial motivation of the employees of the South Kazakhstan Medical Academy (SKMA) and their scientific and publication activities. Methods: An analysis of the publication activity of SKMA employees for the 2018-2020 period was carried out. Based on the "Regulations on reimbursement of expenses and payment of remuneration for the publication of research results in the scientific journals and proceedings" developed in the SKMA, data from the accounting department of the SKMA, which made payments annually and quarterly, from 2018 to 2020, were used and processed. Results: While in 2018 the number of publications in the Scopus and Web of Science databases was 21, thereafter in 2019 this number was increased by 12.5%, and in 2020 - by 40% (compared to 2018). In 2021, there was a decrease in the total number of articles by 14.3% compared to 2020. However, the number of articles in the Q1-Q2 Web of Science journals in 2021 almost doubled compared to 2020. For publications in 2018, an amount of 1,076,350 tenge was paid in the form of remuneration, which in 2019 and 2020 increased to 1,300,120 and 1,845,480 tenge respectively. A positive and statistically significant relationship was found between the number of published papers and the amount of the respective remuneration (r=0.97; p<0.05). Conclusion: The proposed system of motivation in SKMA is an effective stimulating mechanism and can be used to intensify publication activity in other universities, including non-medical ones.